Generic competitive strategies from a Qur’anic perspective - Mhd. Sarif, Suhaimi (World Academy of Islamic Management (WAIM), 2018)
This paper explores generic competitive strategies from Qur’anic perspectives as alternative view. This approach attempts to purify the conventional concept of strategic management, which is a business competitive strategy from a Qur’anic postulate. The process of purification could be done by understanding Islam, organizational realities, and man. When comes to practices, man plays a vital role in integrating Islam into organizational realities. Hence, the most apparent element that needs to be purified is man who is managing, coordinating, and making the objectives a successful reality. The Qur’an has outlined ways and means of managing competitiveness that established justice, fairness and harmony.